Unraveling microbial processes involved in carbon and nitrogen cycling and greenhouse gas emissions in rewetted peatlands by molecular biology - Gios, Emilie; Verbruggen, Erik; Audet, Joachim; Burns, Rachel; Butterbach-Bahl, Klaus; Espenberg, Mikk; Fritz, Christian; Glatzel, Stephan; Jurasinski, Gerald; Larmola, Tuula; Mander, Ülo; Nielsen, Claudia; et al. (Springer Science and Business Media LLC, 2024)
Restoration of drained peatlands through rewetting has recently emerged as a prevailing strategy to mitigate excessive greenhouse gas emissions and re-establish the vital carbon sequestration capacity of peatlands. Rewetting can help to restore vegetation communities and biodiversity, while still allowing for extensive agricultural management such as paludiculture. Belowground processes governing carbon fluxes and greenhouse gas dynamics are mediated by a complex network of microbial communities and processes. Our understanding of this complexity and its multi-factorial controls in rewetted peatlands is limited. Here, we summarize the research regarding the role of soil microbial communities and functions in driving carbon and nutrient cycling in rewetted peatlands including the use of molecular biology techniques in understanding biogeochemical processes linked to greenhouse gas fluxes. We emphasize that rapidly advancing molecular biology approaches, such as high-throughput sequencing, are powerful tools helping to elucidate the dynamics of key biogeochemical processes when combined with isotope tracing and greenhouse gas measuring techniques. Insights gained from the gathered studies can help inform efficient monitoring practices for rewetted peatlands and the development of climate-smart restoration and management strategies.
Keywords: peatland rewetting; microbial communities; biogeochemical processes; molecular biology; climate change mitigation